Rational design of polymer nanofiber aerogels with aligned micrometer-sized porous structures and their high separation performance. (February 2023) - Ge, Xiaohui; Zhang, Youfang; Li, Xin; Chen, Chao; Jin, Jun; Liang, Tianqi; Liu, Jie; Lei, Weiwei; Shi, Dean
Abstract: In this article, a new type of pre-oxidized polyacrylonitrile/polyimide (OPAN/PI) nanofiber aerogels (NFAs) with aligned micrometer-sized hierarchical porous structures was fabricated via oriented ice-segregation-induced self-assembly and thermal imidization process. Polyimide was chosen as an adhesive and cross-linker because of its excellent chemical resistance, thermal stability and mechanical strength. The resulted OPAN/PI NFA have good resilience and high hydrophobicity (water contact angle 136.0°), ultralow density (8.65 mg m −3 ), which can be used as good oil absorbents and efficient separation of oil and water. The optimized OPAN/PI NFAs can collect various oily solvents with high absorption capacities up to 135 times of their own weight. Moreover, surfactant-stabilized water-in-oil emulsions and oil/water mixture can be fully separated under gravity driving and the filtration efficiency has only 1% loss after 20 separation processes. The elution flux can be up to 8.7 × 10 5 L m −2 h −1 . This work opens up the avenue of exploring novel for application in the field of oil/water separation. Graphical abstract: Pre-oxidized polyacrylonitrile/polyimide nanofibrous aerogels with aligned micrometer-sized hierarchical porous structures and high hydrophobicity are readily prepared as an efficient oil/water separation filter. Image 1 Highlights: OPAN/PI NFAs with aligned micrometer-sized hierarchical porous structures are fabricated. Oriented macropores can reduce the emulsion path and increase the flux. The NFAs show high separation efficiency of nearly 100% and high flux of 8.7 × 10 5 L m −2 h −1 .